2021
DOI: 10.1353/hpu.2021.0013
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Exploring the Repercussions on Federally Qualified Health Center Service Delivery and Quality

Abstract: Th e COVID-19 pandemic has brought about a precipitous transformation in health care delivery in the nation's safety-net, primary care system of federally qualifi ed health centers (FQHCs). Th is study uses electronic health record data to quantify the extent of changes to visit volume in 36 FQHCs across 19 states as well as changes in quality metrics. We found a steep decline in in-person visits in March 2020 accompanied by a sharp increase in telehealth visits; however, combined volume remained 23% below pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…Clinics experienced high no-show rates for visits and needed to learn how to support and provide telehealth audio and video encounters, while remaining open for patients needing in-person visits or facing barriers to telehealth use. One study reported that overall FQHC utilization across the U.S. decreased 23% ( Simon et al, 2021 ). Local FQHCs became focal points for testing sites and vaccine campaigns, stretching existing resources and further limiting the availability of preventative and chronic care ( Simon et al, 2021 ).…”
Section: Challenge 1: Impact Of the Pandemic On Clinical Resources An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Clinics experienced high no-show rates for visits and needed to learn how to support and provide telehealth audio and video encounters, while remaining open for patients needing in-person visits or facing barriers to telehealth use. One study reported that overall FQHC utilization across the U.S. decreased 23% ( Simon et al, 2021 ). Local FQHCs became focal points for testing sites and vaccine campaigns, stretching existing resources and further limiting the availability of preventative and chronic care ( Simon et al, 2021 ).…”
Section: Challenge 1: Impact Of the Pandemic On Clinical Resources An...mentioning
confidence: 99%
“…One study reported that overall FQHC utilization across the U.S. decreased 23% ( Simon et al, 2021 ). Local FQHCs became focal points for testing sites and vaccine campaigns, stretching existing resources and further limiting the availability of preventative and chronic care ( Simon et al, 2021 ).…”
Section: Challenge 1: Impact Of the Pandemic On Clinical Resources An...mentioning
confidence: 99%
“…10 A study that assessed the shift in visit volume from in-person to virtual encounters in 36 FQHCs across 19 states found that virtual visits (telephone, video) with a medical, dental, or behavioral health provider increased 3405% from February 2020 to April 2020. 11 The aim of this study is to explore patient experiences and perspectives with receiving care in FQHCs during the shift to telemedicine in primary and behavioral health care during COVID-19. Despite robust literature on telemedicine, studies specifically focused on patients' perspectives on telemedicine visits in primary care [12][13][14] and behavioral health care [15][16][17] are fairly limited and often focused on highly selected populations (e.g., veterans with access issues).…”
Section: Introductionmentioning
confidence: 99%
“…16–22 Clinicians could have been morally distressed by the many patients who, out of fear of being infected by coming to their health provider’s office, delayed or forewent needed office visits and care, including for heart attacks and cancer treatment. 20 23–25 Further, for the many months when adequate personal protective equipment (PPE) was unavailable for healthcare providers in the USA and vaccines not yet available to provide protection, many clinicians in both outpatient and inpatient settings could have felt that they had violated their duty to themselves simply by continuing to see patients and thereby risking becoming infected, and then infecting their families. 12–14 26–28 Moral distress during the pandemic can have important consequences for clinicians, as moral distress is associated with disengagement from patients, compassion fatigue and poorer quality of care, 29 30 poorer clinician mental health and burnout, 13 29 31–33 and job dissatisfaction and turnover.…”
Section: Introductionmentioning
confidence: 99%
“…We are aware of no studies that have assessed moral distress during the pandemic specifically among outpatient clinicians, but such distress is easy to imagine. Outpatient offices in the USA were commonly closed early in the pandemic and then reopened but operated with restricted services and altered care standards to promote safety for more than a year, and these changes may have made outpatient clinicians feel that they were violating their core moral duties to patients of beneficence and non-maleficence, that is, to help patients to the best of their ability and not cause them harm 16–22. Clinicians could have been morally distressed by the many patients who, out of fear of being infected by coming to their health provider’s office, delayed or forewent needed office visits and care, including for heart attacks and cancer treatment 20 23–25.…”
Section: Introductionmentioning
confidence: 99%